Traffic Light Control System Design Using Omron PLC With Ladder Diagram Method - Azpadli Rozali (Cattleya Darmaya Fortuna, 2020)
At this time, traffic congestion is a problem that many big cities face, especially at intersections. Traffic jams at intersections occur a lot because they are caused by the traffic light regulation system that is not in accordance with the traffic light settings which can be changed at any time. The design of the traffic light simulation control program is deviated by four. The program is made with 4 models, namely the all-light flashing model, the flashing yellow light model, and a different one-way model. The current traffic light regulation mostly uses a fixed time setting system where the lights are set to work on a fixed time basis, regardless of the ups and downs of traffic flow. Therefore, offered a detector system (traffic actuated) by utilizing PLC (programmeble logic controller) as a controller. This research is made a simulation tool with PLC Omron. The working process of this tool is in the form of sending input from sensors installed on the road, where this sensor detects the presence or absence of vehicles.